Types of Figurative Language found in Rosé’s Selected Songs - I Putu Prema Bagastia; I Made Yogi Marantika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines figurative language contained in Rose´’s selected songs. Figurative language uses words or expressions with a meaning that is different from the literal interpretation. It aims to analyze the types of figurative language and the meaning of figurative language. The data source in this study was taken from two selected songs from Rose´. A qualitative method was used in this study. To solve the problem, this study employs Abrams and Harpham’s (2005) theory types of figurative language including simile, metaphor, metonymy, hyperbole, irony, paradox, and allusion and Leech’s (1981) theory meaning of figurative language. In this study, six types of figurative language were found namely metaphor, irony, metonymy, hyperbole, allusion, and paradox. The results and discussion in this study reveal 18 types of figurative language consisting 50% of metaphor, 22,22% of irony, 11,11% of metonymy, and 5,5% each of hyperbole, allusion, and paradox. This study may enhance the comprehension of figurative language in modern music and provide valuable input for learners of English in interpreting song lyrics more effectively.